Successful coronary lithotripsy after unsuccessful rotational atherectomy – use of complementary tools for treatment of undilatable calcified coronary artery stenosis - M. Wańczura, Piotr; Wojakowski, Wojciech (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Despite the progress in percutaneous treatment of coronary artery disease, massively calcified atherosclerotic lesions still constitute a challenge. Rotational atherectomy, capable of modifying the atherosclerotic plaque, known as debulking, has become the gold standard in the treatment of calcified lesions [1]. Recently, intravascular lithotripsy (IVL) became an alternative treatment option for undilatable calcified vessels. This technique uses a balloon-mounted ultrasound source which emits sonic pressure waves propagating through the fluid and delivered to the vessel wall. It results in fragmentation of superficial and deep calcium deposits allowing balloon expansion [2].